2015
DOI: 10.1016/j.joca.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes is a risk factor for knee osteoarthritis progression

Abstract: Type 2 diabetes was a predictor of joint space reduction in men with established knee OA. No relationships were found between MetS or other metabolic factors and radiographic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
117
5
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 71 publications
3
117
5
18
Order By: Relevance
“…This observation was similar to the findings of Eymard et al, (11) who found that increased BMI and weight bring about increased pain intensity in patients with knee Osteoarthritis. OA is increasingly considered as a systemic disease, especially in terms of a possible relationship to metabolic disorders linked to obesity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation was similar to the findings of Eymard et al, (11) who found that increased BMI and weight bring about increased pain intensity in patients with knee Osteoarthritis. OA is increasingly considered as a systemic disease, especially in terms of a possible relationship to metabolic disorders linked to obesity.…”
Section: Discussionsupporting
confidence: 92%
“…OA is increasingly considered as a systemic disease, especially in terms of a possible relationship to metabolic disorders linked to obesity. Obesity is one of the risk factors for knee OA, since mechanical overload on weightbearing joints activates chondrocytes and accelerates cartilage degeneration (11). The knee is a weight bearing joint and obesity increases the loading of the knee joints which then speeds up the rate of degeneration of the articular components of the knee increasing the risk of knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these features is supported by previous non-phenotyping studies that identified an association between high BMI and OA lesions in non-weight-bearing joints suggesting an underlying systemic pathway [48]. Moreover, recent studies showed that the combination of cardio-metabolic disturbance and obesity increases the risk of OA and identified an association between OA and hypertension, dyslipidaemia, and hyperglycaemia [46,[49][50][51]. These findings indicate that systemic metabolic alterations could be one of the main causes for the disease in a specific subgroup of subjects.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have demonstrated that DM may favor the development or progression of OA. [5][6][7][8][9] For example, when chondrocytes are exposed to high glucose levels over a longer period of time, they are unable to downregulate GLUT-1 protein, and therefore accumulate glucose and produce more reactive oxygen species (ROS). 37 An intracellular increase of glucose and ROS are major mediators for cartilage destruction, which can promote cartilage degeneration.…”
Section: Chanchek Et Al: Diabetes and Cartilage Degenerationmentioning
confidence: 99%
“…4 Previous studies have suggested that DM or hyperglycemia is a probable risk factor and prognostic predictor for OA. [5][6][7][8][9] The…”
mentioning
confidence: 99%